Risk indentification on superheater pipeline boiler of 600 MW power plants using a risk based inspection (RBI) method - Rahman, Okky Helja Octora Syahida; Pratama, Fikri Wahyu; Siradj, Eddy S (Universitas Negeri Padang, 2022)
Steam power plants are the most efficient type of power generation and can make a significant contribution to the demand for electricity resources. Steam power plants, in general, utilize energy derived from seawater to be process into steam in boilers so that often many pipe failures have occurred due to thinning due to corrosion caused by inappropriate water quality in small units and difficult to detect continuously. In general, inspection planning related to pipe thinning in steam power plants shows a minimal trend compared to inspections in the oil & gas industry. Moreover, it has no basic policy as to how inspection intervals and piping methods will be carry out. In this study, it carried out with the aim of conducting a risk assessment of boiler pipe failure so that it can provide a more optimal overview of the inspection plan. Analysis using Risk Based Inspection (RBI) will be used as a research reference to create the most effective and efficient inspection system as to minimize the impact and expenses cost in pipeline maintenance. After RBI assessment, the inspection plan for superheater pipeline on boiler line will be held every 2 years.